Retrospective Outcome Monitoring of ADHD and Nutrition (ROMAN): The Effectiveness of the Few-Foods Diet in General Practice - Pelsser, Lidy; Frankena, Klaas; Toorman, Jan; Rodrigues Pereira, Rob (Frontiers in Psychiatry, 2020)
Introduction Double-blind placebo-controlled studies investigating the effect of a few-foods diet (FFD) on attention-deficit/hyperactivity disorder (ADHD) have provided consistent evidence that ADHD can be triggered by foods, indicating the existence of a food-induced ADHD subtype. In 2001 the ‘few-foods’ approach was included in an ADHD treatment protocol. This approach consists of a) determining, by means of an FFD, whether food is a trigger of ADHD; b) reintroducing, in FFD responders, foods to assess which foods are incriminated; c) finally composing a personalised diet eliminating the involved foods only. In the Netherlands the few-foods approach is applied in practice. We aimed to retrospectively assess its effectiveness on ADHD and oppositional defiant disorder (ODD) in real life. Methods Data from all children who started the few-foods approach in three specialised healthcare facilities during three consecutive months were included. Behaviour was assessed at start and end of the 5-week FFD, using the ADHD Rating Scale and a structured psychiatric interview. Clinical responders (behavioural improvements ≥ 40%) proceeded with the reintroduction phase. Results Data of 57 children, 27 taking medication and 15 following some elimination diet at start, were available. No differences were noted between parental scores of children with and without medication or some elimination diet at start. 21/27 (78%) children stopped taking medication during the FFD. 34/57 (60%) children were ADHD responders, 20/29 (65%) children meeting ODD criteria were ODD responders. 26/34 (76%) ADHD responders started the reintroduction phase; 14/26 (54%) still participated at six months. Teacher data were available of 18/57 (32%) children. 9/18 (50%) children were ADHD responders. Conclusion The FFD, if applied by trained specialists, may lead to clinically relevant reduction of ADHD and ODD symptoms in general practice, and a concomitant decrease of ADHD medication. These results corroborate the existence of an ADHD subgroup with food-induced ADHD. Defining and eliminating the incriminated foods, i.e. the underlying causal triggers, may result in secondary prevention of food-induced ADHD. Research into underlying mechanism(s) is of vital importance: finding an easier method or biomarkers for diagnosing food-induced ADHD and ascertaining the incriminated foods may lead to redundancy of the few-foods approach.